A dog's promise [compact disc, unabridged] - Cameron, W. Bruce (Cameron, W. Bruce. Dog's purpose novel., 2019)
The dog who thinks of himself as 'Bailey' knows one thing for sure: all dogs go to heaven after they have fulfilled their purpose on earth. But Bailey's work on earth is far from finished, there are still so many more humans that need a dog's talent for unconditional love. There is one family in particular that needs Bailey's help, a family that is on the verge of breaking apart. But if Bailey helps this family he won't remember his previous lives, the connections he's made, and the humans he's met and loved. Bailey must decide whether to sacrifice everything to heal this one, desperate family.